Dynamic simulation of a full vehicle system featuring magnetorheological dampers with bypass holes. (January 2020) - Oh, Jong-Seok; Kim, Key-Sun; Lee, Yang-Sup; Choi, Seung-Bok
This study suggests a relationship between two different types of magnetorheological dampers and the driving performance of the passenger vehicles such as ride quality and stability. One of the magnetorheological dampers has the two different bypass holes in the piston bobbin to achieve a relatively low damping force slope in the low piston velocity region. Without bypass holes, two cylindrical-type magnetorheological dampers have same dimensions (pole lengths, piston radius, and coil size). To enhance the ride quality of the passenger vehicle, the damping force slope of the magnetorheological damper with bypass holes is more gradual than that of the magnetorheological damper without bypass holes. On the basis of the damping force model, three vehicle types with two working modes (soft and hard) are formulated. Driving performance indexes, such as vertical acceleration of the sprung mass and tire deflection, are evaluated in frequency domains under two random road conditions. A comparative study is conducted to prove the effectiveness of the magnetorheological damper with bypass holes through simulation.